Post‐transplant lymphoproliferative disorder following kidney transplantation: a population‐based cohort study. (18th February 2016) - Maksten, Eva Futtrup; Vase, Maja Ølholm; Kampmann, Jan; d'Amore, Francesco; Møller, Michael Boe; Strandhave, Charlotte; Bendix, Knud; Bistrup, Claus; Thiesson, Helle Charlotte; Søndergaard, Esben; Hamilton‐Dutoit, Stephen; Jespersen, Bente
Summary: Post‐transplant lymphoproliferative disorder (PTLD) incidence is difficult to determine, mainly because both early and other lesions may go unrecognized and unregistered. Few studies have included systematic pathology review to maximize case identification and decide more accurately PTLD frequency after long‐term post‐transplantation follow‐up. A retrospective population‐based cohort study including all kidney transplant recipients at two Danish centres (1990–2011; population covered 3.1 million; 2175 transplantations in 1906 patients). Pathology reports were reviewed for all patient biopsies to identify possible PTLDs. Candidate PTLDs underwent histopathological review and classification. Seventy PTLD cases were identified in 2175 transplantations (3.2%). The incidence rate (IR) after first transplantation was 5.4 cases per 1000 patient‐years (95% CI: 4.0–7.3). Most PTLDs were monomorphic (58.5%), or early lesions (21.5%). Excluding early lesions and patients <18 years, IR was 3.7 (95% CI: 2.9–5.5). Ten patients with PTLD were retransplanted, 2 developing further PTLDs. Post‐transplant patient survival was inferior in patients with PTLD, while death‐censored graft survival was not. Using registry data together with extensive pathological review and long follow‐up, a rather high incidence of PTLD was found.